Localized prostate cancer and robot-assisted laparoscopic radical prostatectomy: a retrospective, comparative study between pre- and post-operative Gleason scores. Issue 1 (2nd January 2018) - Henderickx, Michaël M. E. L.; Brits, Tim; Muilwijk, Tim; Adams, Thomas; Vandeursen, Hendrik
Abstract: Introduction: To compare the pre- and post-operative Gleason scores (GS) in patients with localized prostate cancer treated with robot-assisted laparoscopic radical prostatectomy. Materials and methods: A single center, retrospective comparison between pre- and post-operative GS. Age, prostate volume, PSA, number of biopsies, number of positive cores, biopsy GS, cTNM, final pathology GS and pTNM of 286 patients were retrieved. They were divided into risk groups. Results: A total of 286 patients with a mean age at surgery of 64.64 ± 7.81 y and mean PSA-value of 9.35 ± 8.38 ng/mL. Mean prostate volume was 55.09 ± 24.93 mL, mean number of biopsies was 11.90 ± 4.63. Mean percentage of positive cores was 36.90 ± 22.42%. A GS of <7 was seen in 23.4%, 66.8% had a GS of 7 and 9.7% of >7 in final pathology. Of the total, 38.1% were pre-operative low risk, 58.7% of them had an upgrade in GS on final pathology, 45.1% were in the intermediate risk group, 5.4% showed a downgrade, 64.3% remained stable and 30.2% had an upgrade in GS. Also, 16.8% were high risk patients of which 35.4% had a downgrade, 39.6% remained stable and 25% showed an upgrade of the GS. Conclusions: We found a substantial underestimation of the GS in the pre-operative setting when compared to the GS in final pathology.